Miracle in a dry season - Thomas, Sarah Loudin (2014)
"In small town West Virginia, 1954, one newcomer's special gift with food produces both gratitude and censure. Will Perla Long and her daughter find a home there?"--
Keywords: Single mothers -- Fiction; Bachelors -- Fiction; Women cooks -- Fiction; Public opinion -- Fiction; West Virginia -- Fiction; Christian fiction; Love stories